Vista of Metz, France - Published by Foriss'er | G (Wikimedia Commons, 1919)
Carte postale ancienne issue de Wikimedia Commons. Titre: Vista of Metz, France. Photo postcard is an bird's eye view of the Skyline of Metz, France. Clearly Visible are the steeples of three churches
Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; Patrimoine; Histoire Locale; Wikimedia Commons; église